Radioiodine-Refractory Thyroid Cancer: Molecular Basis of Redifferentiation Therapies, Management, and Novel Therapies - Aashiq, Mohamed (Cancers (Basel), 2019)
Recurrent, metastatic disease represents the most frequent cause of death for patients with thyroid cancer, and radioactive iodine (RAI) remains a mainstay of therapy for these patients. Unfortunately, many thyroid cancer patients have tumors that no longer trap iodine, and hence are refractory to RAI, heralding a poor prognosis. RAI-refractory (RAI-R) cancer cells result from the loss of thyroid differentiation features, such as iodide uptake and organification. This loss of differentiation features correlates with the degree of mitogen-activated protein kinase (MAPK) activation, which is higher in tumors with BRAF (B-Raf proto-oncogene) mutations than in those with RTK (receptor tyrosine kinase) or RAS (rat sarcoma) mutations. Hence, inhibition of the mitogen-activated protein kinase kinase-1 and -2 (MEK-1 and -2) downstream of RAF (rapidly accelerated fibrosarcoma) could sensitize RAI refractivity in thyroid cancer. However, a significant hurdle is the development of secondary tumor resistance (escape mechanisms) to these drugs through upregulation of tyrosine kinase receptors or another alternative signaling pathway. The sodium iodide symporter (NIS) is a plasma membrane glycoprotein, a member of solute carrier family 5A (SLC5A5), located on the basolateral surfaces of the thyroid follicular epithelial cells, which mediates active iodide transport into thyroid follicular cells. The mechanisms responsible for NIS loss of function in RAI-R thyroid cancer remains unclear. In a study of patients with recurrent thyroid cancer, expression levels of specific ribosomal machinery—namely PIGU (phosphatidylinositol glycan anchor biosynthesis class U), a subunit of the GPI (glycosylphosphatidylinositol transamidase complex—correlated with RAI avidity in radioiodine scanning, NIS levels, and biochemical response to RAI treatment. Here, we review the proposed mechanisms for RAI refractivity and the management of RAI-refractive metastatic, recurrent thyroid cancer. We also describe novel targeted systemic agents that are in use or under investigation for RAI-refractory disease, their mechanisms of action, and their adverse events.